The prevalence of musculoskeletal disorders and low back pain among Italian nurses: An observational study.: Low Back Pain Among Italian Nurses - Latina, Roberto; Petruzzo , Antonio; Vignally, Pascal; Cattaruzza, Maria Sofia; Vetri Buratti, Carlo; Mitello, Lucia; Giannarelli, Diana; D'Angelo, Daniela (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Musculoskeletal disorders and low back pain have negative impact amongst Italian nurses who work in hospital. Nursing staff are known to be at risk of developing back disorders, where low back pain has a prevalence from 16% to 60% in the world. This study aims to determine the prevalence of musculoskeletal disorders and low back pain among nurses who working in a Roman hospital. Methods: Cross sectional study was carried out in an Italian hospital and the Nordic Musculoskeletal Questionnaire-IRSST was administered to 256 registered nurses. Logistic regression analyses were performed to understand risk factors associated with pain. Results: Nurses reported different locations of pain related to musculoskeletal disorders. The prevalence of low back pain was 90.2% during life, 80% during the last year and 44.5% during the last week. Female sex increases the risk of being affected by low back pain (OR = 2.07, 95% CI= 1.00-4.32). Conclusions: Musculoskeletal disorders and low back pain are reported by the majority of nurses interviewed, and a higher prevalence is observed in women. Pain does not depend on the amount of years of work, nor on age or body mass index. In order to assess the prevalence of low back pain carefully, it is recommended to study a greater number of Italian nurses in different hospitals.